2021
DOI: 10.1016/j.addma.2021.102050
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphological properties of additively manufactured SS316L and Ti6Al4V micro-struts as a function of build angle

Abstract: Additive manufacturing methods such as laser powder bed fusion (PBF) can produce micro-lattice structures which consist of ‘micro-struts’, which have properties that differ from the bulk metal and that can vary depending on the orientation of the strut to the build direction (the strut build angle). Characterizing these mechanical and morphological changes would help explain macro-scale lattice behavior. Individual stainless steel (SS316L) and titanium alloy (Ti6Al4V) laser PBF struts were built at 20°, 40°, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…As the gyroid structure may be the most similar to cancellous bone, other lattice structures, with similar micro‐structure to gyroid, should be tested to further fine‐tune this model. Previous studies have demonstrated that lattice structures can be individually altered to change the material properties in different planes and orientations 93–95 . These methods can be applied to the present model to further fine‐tune the properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the gyroid structure may be the most similar to cancellous bone, other lattice structures, with similar micro‐structure to gyroid, should be tested to further fine‐tune this model. Previous studies have demonstrated that lattice structures can be individually altered to change the material properties in different planes and orientations 93–95 . These methods can be applied to the present model to further fine‐tune the properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that lattice structures can be individually altered to change the material properties in different planes and orientations. 93 , 94 , 95 These methods can be applied to the present model to further fine‐tune the properties. Finally, the overall structural strength of the model should be validated against cadaveric cervical spine specimen.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the need for supports for the lattice structure, which would result difficult to be removed, the lattice structures could be angled for production, but it is not possible to define an ideal printing orientation due to the variable orientation of the conformal lattice. Nevertheless, recent studies have shown that small sizes of the beam may not require the use of supports [82,83], so considering the size of the beams of the studied lattice structures, it might be possible to produce them vertically by SLM technologies.…”
Section: Structural Analysis Validationmentioning
confidence: 99%
“…SS316L has been commonly used in a wide range of industrial applications considering its high strength, high oxidation and corrosion resistance and good heat resistance (Bautista et al , 2003; Choi et al , 2015; Simchi et al , 2006). Generally, SS316L has been fabricated by BJT for applications such as electrochemical or bio-medical (Gokuldoss et al , 2017) or depending upon the application; it can also be fabricated using BJT (Frykholm et al , 2016) or LPBF (Hossain et al , 2021; Lin et al , 2020; Alharbi, 2022).…”
Section: Introductionmentioning
confidence: 99%